Effect of testicular thermoregulation on the quality of buffalo sperm - Neto, Carlos Ramires [UNESP]; Monteiro, G. A. [UNESP]; Sancler-Silva, Y. F.R. [UNESP]; Resende, H. L. [UNESP]; Zorzetto, M. F. [UNESP]; Oba, E. [UNESP] (My University, 2013)
The process of spermatic division and differentiation (spermatogenesis) occurs with intratesticular temperature lower that the corporal temperature and for that is essential that the testicular thermoregulation mechanism occurs properly. For evaluation of the scrotal surface temperature can be used the infrared thermography or testicular sensors, besides that, can be evaluated the blood flux in the spermatic cord through the Doppler ultrasonography. Thus, the aim of this study is to analyze the testicular thermoregulation in adult buffaloes through scrotal thermography and Doppler ultrasound of testicular artery and verify its effect on sperm quality. For that were used seven healthy buffaloes, with age of 3 and 4 years, of the Murrah breed. The animals were subjected to 3 semen collections using artificial vagina, with one day of interval. In addiction, the retal temperature measurement (RT) with dry bulb thermometer, the measurement of scrotal surface temperature (SST) and body surface temperature (BST) through infrared thermography and the pulsatility (PI) and resistivity (RI) index of testicular artery by Doppler ultrasonography, were performed using 2 distinct moments: animals previously placed to shade (M1) and animals subjected to 4 hours of sun (M2). All parameters were compared by T test and the correlations were performed by Pearson test using the In Stat Graph Pad 3® program. The significant level considered was 5%. There was an increase (p<0,05) of RT, SST, SNT and RI in M2. increasing trend was observed (0,05>p>0,01) PI and RI between M1 and M2. There was a low correlation between SST and semen quality. The results of this study allow us to conclude that adult buffaloes have low ability to perform body and testicular thermoregulation in situations of enviromental heat stress. However, this low capacity of testicular temperature maintenance demonstrated no correlation with the sperm kinetic parameters and sperm morphological defects in buffalo spermatozoa.
Keywords: Buffalo; Doppler ultrasonography; Semen; Testicular thermoregulation; Thermal stress; Thermography